Multiuser private queries over encrypted databases. (1st September 2009) - Yang, Yanjiang; Bao, Feng; Ding, Xuhua; Deng, Robert H.
Searchable encryption schemes allow users to perform keyword-based searches on an encrypted database. Almost all existing such schemes only consider the scenario where a single user acts as both the data owner and the querier. However, most databases in practice do not just serve one user; instead, they support search and write operations by multiple users. In this paper, we systematically study searchable encryption in a practical multiuser setting. Our results include a set of security notions for multiuser searchable encryption as well as a construction which is provably secure under the newly introduced security notions. We also discuss how to improve query efficiency.